Bta-miR-124a Affects Lipid Metabolism by Regulating PECR Gene. (28th July 2019) - Shen, Binglei; Yang, Zhuonina; Han, Shuo; Zou, Ziwen; Liu, Juan; Nie, Lian; Dong, Wentao; Li, E.; Liu, Shengjun; Zhao, Zhihui; Wu, Rui
Abstract : According to our previous studies, bta-miR-124a was differentially expressed in breast tissue between high-fat and low-fat dairy cows. However, the function of bta-miR-124a in lipid metabolism of dairy cows and the identification of its target genes have not been reported. Therefore, this study will identify the target gene of bta-miR-124a and explore its role in the regulation of milk lipid metabolism. First, preliminary bioinformatics prediction of bta-miR-124a candidate target genes was performed, and quantitative real-time polymerase chain reaction (qRT-PCR) was used to analyze relative expression changes of bta-miR-124a and its candidate target genes and the expression level of the downstream gene of the target gene in the lipid metabolism signaling pathway in dairy mammary epithelial cell lines (Mac-T), using the dual luciferase reporter system for the identification of the targeting relationship between bta-miR-124a and the candidate target gene. Then, the effect of transfection of bta-miR-124a mimics and inhibitors on triglyceride (TG) and free fatty acid (FFA) levels was analyzed. The results indicate that bta-miR-124a directly interacts with the 3′-untranslated region of peroxisomal trans-2-enoyl-CoA reductase ( PECR ) to downregulate its expression in Mac-T cells. Further, bta-mir-124a regulates the expression of PECR and the downstream gene extension of very long chain fatty acid protein 2 ( ELOVL2 ) through an unsaturated fatty acid biosynthesis signaling pathway. In conclusion, bta-miR-124a is involved in lipid metabolism by directly downregulating the PECR gene and affecting the expression of the downstream gene ELOVL2 and regulates the content of some key secretory elements such as TG and FFA. The function of bta-miR-124a has a certain effect on the synthesis and secretion of milk fat in the mammary epithelial cells of dairy cows.